Peran Kepemimpinan Kepala Sekolah dalam Mengimplementasikan Merdeka Belajar di Sekolah Dasar - Maisaroh; Ratnasari, Wienda; Fitrianti; Lebang, Rita; Dwiyono, Yudo (SISTEMA: Jurnal Pendidikan, 2024)
The role and responsibilities of the school principal are very crucial in achieving learning goals. This study aims to improve understanding of the functions and leadership of school principals in achieving educational goals. In addition, this study also attempts to examine the influence of principal leadership on achieving educational goals. No field survey was conducted in this study. Instead, researchers collected data from books, magazines, articles, and other sources relevant to the principal's duties in achieving goals in elementary schools. They also reviewed previous research. The results of the study revealed that (1) the principal formulates school policy strategies and methods to achieve educational goals, and (2) the role of the principal has great significance for school success. This program was initiated by Nadiem Makarim, Minister of Education, Culture, Research, and Technology.